Implementasi Hukum Atas Pembebanan Biaya Dalam Transaksi Quick Response Code Indonesian Standard (QRIS) - Ariani, Deva Vira; Utomo, Setiyo; Gegana, Reza Pramasta (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In QRIS services, Bank Indonesia imposes two types of fees that must be paid by merchants or business actors as QRIS users: the Merchant Discount Rate (MDR) fee and the transaction settlement fee. The MDR fee is a fee borne by business actors in QRIS payment transactions. This study uses a socio-legal approach that focuses on business actors, QRIS users, Bank Indonesia, the Financial Services Authority, Bank BCA, Bank Kaltimtara, and Bank BNI. The primary data source is the results of interviews with business actors, QRIS users, Bank Indonesia, the OJK, Bank BCA, Bank Kaltimtara, and Bank BNI. Secondary and tertiary data were obtained through a literature review to collect legal materials relevant to the study. The results of this study indicate that despite the existence of regulatory policies, legal protection for consumers in cases of charging additional fees outside the agreement on transactions using the Indonesian Standard Quick Response Code (QRIS) is not yet fully effective, both from a preventive and repressive perspective. The implementation of regulations related to the Merchant Discount Rate (MDR) fee has not been optimally implemented by the competent authorities in the QRIS payment system.